Estresse em fisioterapeutas de Goiânia - GO - Silva, Patricia Leite Alvares (2015)
This thesis follows the scientific article model. The first article is entitled "Occupational stress in physiotherapists: integrative review" and was submitted to Science and Public Health journal. Objectives: select, evaluate and critically analyze the publications that have focused on stress therapists. Methods: This is an integrative review, using the key words: burnout; Professional wear; professional burnout; occupational stress; professional stress; emotional exhaustion; physical exhaustion; professional exhaustion; job satisfaction; quality of life. Inclusion criteria were: studies that investigated the occupational stress experienced by physiotherapists from any area of operation without time limit; articles in Portuguese, English or Spanish. Results: 409 studies were identified, we proceeded to read the title, description and summary to make the selection. They remained 35 articles, and of these, selected and evaluated nine studies that show that the work of physiotherapy professional features is exposed to stress and the factors related to occupational stress. They also identified the main physical and emotional symptoms such as headache, muscle and joint pains, stomach problems, fatigue, decreased concentration, nervousness, anxiety and sleep disorders. Regarding coping with stress, strategies cited by physiotherapists were: exercise, leisure, vacation, blame others, alcohol, share problems with peers and / or superiors; part course on stress management; Massage and financial independence. The articles highlight an inherent complexity to the characteristics of the profession that carries a high risk of physical, mental and emotional ailments linked to an occupational activity, which reinforces the need to incorporate the theme in the academic training of physiotherapists for preventing and coping with occupational stress. The second article to be submitted to the Public Health Notebooks magazine is entitled "Factors associated with stress in physical therapists." Objectives: The objective of this study was to investigate the existence and the level of stress in physical therapists from the city of Goiania-Go and identify the presence of predominant symptoms and associate the presence of stress and sociodemographic variables. Methods: A cross-sectional descriptive study of 401 physiotherapists in the city of Goiania. Two instruments were used a sociodemographic questionnaire and the Inventory of Stress Symptoms for Adults Lipp (ISSL) in the period from July 2013 to October 2014. Results: The stress was identified in 56.6% physiotherapists, and of these, 82 , 0% were in the resistance phase and psychological symptoms was found in 67.4% of participants. There was a greater distribution of stress among female physiotherapists (n = 192; 85%; p <0.001), who are dissatisfied with physical therapy (n = 87; 38.5%; p <0.001) and those who attribute stress to labor (n = 95; 42%; p <0.001). The results are discussed considering the associations between stress and labor activity of the physiotherapist. It was observed that physiotherapists in the work environment, are exposed to factors that lead to stress. Thus, there is need for action, particularly in the recognition of stressors, in order to develop mechanisms for effective coping in order to reduce the psychological and physical impact of stress.